2009
DOI: 10.1080/10286020903042358
|View full text |Cite
|
Sign up to set email alerts
|

Guaiane-type sesquiterpenes fromCurcuma wenyujinand their inhibitory effects on nitric oxide production

Abstract: Four new guaiane-type sesquiterpenes (1S,4S,5S,10R)-zedoarondiol, zedoalactones D, E, and F (1-4), along with 10 known ones (5-14), were isolated from Curcuma wenyujin Y.H. Chen et C. Ling. The structures of these new compounds were elucidated by spectroscopic methods. The inhibitory effects of compounds 1-14 on nitric oxide production in lipopolysaccharide-activated macrophages were evaluated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 24 publications
1
37
0
Order By: Relevance
“…The isolation of CHCl 3 fraction of C . zedoaroides yielded one new guaiane sesquiterpene lactone ( 4 ), one new diarylheptanoid ( 7 ), and five known guaiane sesquiterpene lactones: gweicurculactone ( 1 ; Jiang et al, ; Phan, Tran, Phan, Matsunami, & Otsuka, ; Wu et al, ; Zhang, Ji, Ji, & Fan, ), zedoalactone B ( 2 ; Takano, Yasuda, Takeya, & Itokawa, ), phaeocaulisin C ( 3 ; Liu et al, ), zedoalactone H ( 5 ; Wu et al, ), and zedoalactone E ( 6 ; Liu et al, ; Lou et al, and Wu et al, ). The NMR data of all compounds can be seen in Supporting Information.…”
Section: Resultsmentioning
confidence: 99%
“…The isolation of CHCl 3 fraction of C . zedoaroides yielded one new guaiane sesquiterpene lactone ( 4 ), one new diarylheptanoid ( 7 ), and five known guaiane sesquiterpene lactones: gweicurculactone ( 1 ; Jiang et al, ; Phan, Tran, Phan, Matsunami, & Otsuka, ; Wu et al, ; Zhang, Ji, Ji, & Fan, ), zedoalactone B ( 2 ; Takano, Yasuda, Takeya, & Itokawa, ), phaeocaulisin C ( 3 ; Liu et al, ), zedoalactone H ( 5 ; Wu et al, ), and zedoalactone E ( 6 ; Liu et al, ; Lou et al, and Wu et al, ). The NMR data of all compounds can be seen in Supporting Information.…”
Section: Resultsmentioning
confidence: 99%
“…The first two fractions were repeatedly subjected to column chromatography over silica gel, MCI gel, ODS gel, and semipreparative HPLC to obtain 10 new terpenoids (1−10) and 17 known terpenoids (11−27). The known compounds were identified as zedoarolide B (11), 13 zedoalactone C (12), 13 phaeocaulisin B (13), 14 4βhydroxy-5β-H-guai-1 (10),7 (11),8-trien-12,8-olide (14), 13 gweicurculactone (15), 15 curdionolide A (16), 16 curdionolide B (17), 16 7,8-seco-9 (10),11 (12)-guaiadien-8,5-olide (18), 17 4α,8β-dihydroxy-5α-(H)-eudesm-7(11)-en-8,12-olide (19), 18 isogermafurenolide (20), 19 phacadinane D (21), 20 zedoarondiol (22), 13 wenyujinin B (23), 21 procurcumenol (24), 13 curcumadiol (25), 22 (E)-3-hydroxylabda-8 (17),12-dien-16,15olide (26), 23 and labda-8 (17),13( 14)-dien-15,16-olide ( 27) 24 by comparing their HRESIMS and NMR data with the corresponding data in the cited references, and their structures are shown in Figure S1 in the Supporting Information.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Accumulating researches have already identified the effects of sesquiterpenes of Curcuma zedoaria in preventing inflammatory responses. 12,30 32 Cho et al 33 demonstrated that zedoarondiol, a compound of ZGS, dose dependently inhibited lipopolysaccharide-stimulated tumor necrosis factor α, interleukin (IL) 6, and IL-1β production in RAW 264.7 macrophage and mouse peritoneal macrophage cells by suppressing the phosphorylation of Nuclear factor-kappB (IkappB) kinase (IKK) and Mitogen-activated protein kinases (MAPKs) and subsequently by inactivating the nuclear factor-κB pathway. This demonstrates that ZES prevents inflammation.…”
Section: Discussionmentioning
confidence: 99%